2008
DOI: 10.1080/01612840801904480
|View full text |Cite
|
Sign up to set email alerts
|

Bullying, Burnout, and Mental Health Amongst Portuguese Nurses

Abstract: Bullying is a concept commonly used to describe situations in which an individual is persistently treated in an abusive manner over a period of time, with a feeling of not being able to counterattack or defend him-or herself against the abuse. In this study we investigated both the prevalence of bullying in Portuguese nurses and the relationship between the symptoms of burnout and mental health in nurses who report being bullied. Participants were 107 nurses of the Portuguese Public Health System. We concluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
2
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 19 publications
9
64
2
9
Order By: Relevance
“…In this sense, by creating empowering Work-related bullying was also significantly predictive of new graduates' experiences of both emotional exhaustion and cynicism at Time 2 (controlling for their Time 1 levels). This finding is consistent with previous cross-sectional research that has demonstrated the influence of bullying on employee burnout (Laschinger et al, 2010;Sá & Fleming, 2008). However, this is one of the few studies that has demonstrated this effect when controlling for previous burnout levels.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this sense, by creating empowering Work-related bullying was also significantly predictive of new graduates' experiences of both emotional exhaustion and cynicism at Time 2 (controlling for their Time 1 levels). This finding is consistent with previous cross-sectional research that has demonstrated the influence of bullying on employee burnout (Laschinger et al, 2010;Sá & Fleming, 2008). However, this is one of the few studies that has demonstrated this effect when controlling for previous burnout levels.…”
Section: Discussionsupporting
confidence: 83%
“…Bullying has shown to be stressful and result in higher levels of burnout (Einarsen et al, 1998;Sá & Fleming, 2008). Workplace stress is a common reason why employees …”
Section: Influence Of Workplace Bullying and Burnout On Job And Careementioning
confidence: 99%
“…At the same time they present increased anxiety, depression, propensity to quit their job and symptoms of burnout (9) .…”
Section: Fontes Kb Carvalho Mdbmentioning
confidence: 99%
“…The field of health and medical service is one of the industrial fields where workplace bullying most frequently takes place. In the U.K., 1/6 of the nurses working in hospitals reported that they went through workplace bullying in the past 12 months [11], and in the U.S., 65% of the nurses reported that they witnessed their co-workers being bullied [12]. In South Korea, 23% of the nurses going to graduate school who were interviewed reported that they experienced workplace bullying in the past 6 months [13].…”
Section: Introductionmentioning
confidence: 99%